Biological Activities of Isorhamnetin : A Review - Khaled, Radhed (Plantae Scientia, 2020)
In recent years, flavonols have been a focus of research due to their important biological activities. Isorhamnetinis a flavonol. It belongs to a group of plant secondary metabolites known as flavonoids. It is present in man’s daily diet and is known for its biological activities such as antioxidant, antiviral, anticancer, antimicrobial, anti-Tuberculosis and anti-inflammatory effects. It has been reported for its antioxidant and antiviral applications hence it is not only used as such, but it also has various derivatized forms which has potentials for development into drugs for the treatment of diseases caused by oxidative stress and lethal viruses.